Ordinance Against Increasing Violence Against the Healthcare Providers in Nepal - Parajuli, Bibek Raj; Koirala, Sanjib (Journal of Karnali Academy of Health Sciences, 2022)
Violence against doctors and other health care workers is a global problem. It is increasing in Nepal in recent years. Patients’ relatives and third parties are threatening the doctors and hospital authorities demanding money for dead bodies in the name of negligence. Nepal Medical Association had been raising voice against these kinds of activities for a long time. Recently, an ordinance had been passed by the president of Nepal and tabled in the parliament in May 2022.